Respostas

2014-06-15T19:05:27-03:00
3(x²-1)=2x(x+1)
3x
²-3=2x²+2x
3x²-2x²-2x-3=0
x²-2x-3=0
Usando Bascara:
Δ = b2 - 4.a.c 
Δ = -2² - 4 . 1 . -3 
Δ = 4 - 4. 1 . -3 
Δ = 16

x = (-b +- √Δ)/2a
x' = (-(-2) + √16)/2.1   
x' = 6 / 2   
x' = 3   

x'' = (--2 - √16)/2.1

x'' = -2 / 2

x'' = -1

S={-1 , 3}
A melhor resposta!
2014-06-15T19:50:21-03:00
3 (x² - 1) = 2x (x + 1)
3x² - 3 = 2x² + 2x
3x² - 2x² - 2x - 3 = 0
x² - 2x - 3 = 0

a = 1
b = - 2
c = - 3

Δ = b² - 4ac
Δ = (- 2)² - 4 * 1 * (- 3)
Δ = 4 + 12
Δ = 16

x = - b ± √Δ
    _________  
            2a
x = - (- 2) ± √16
     ___________
            2 * 1
x = 2 ± 4
     ______
         2
x' = (2 + 4) ÷ 2
x' = 6 ÷ 2
x' = 3

x" = (2 - 4) ÷ 2
x" = - 2 ÷ 2
x" = - 1

Resposta: {3; -1}
1 5 1